Deleuze and Guattari's Anti-Oedipus : introduction to schizoanalysis - Deleuze, Gilles, 1925-1995 (Routledge, 1999)
Eugene W. Holland provides an excellent introduction to Gilles Deleuze and Felix Guattari's Anti-Oedipus which is widely recognized as one of the most influential texts in philosophy to have appeared in the last thirty years. He lucidly presents the theoretical concerns behind Anti-Oedipus and explores with clarity the diverse influences of Marx, Freud, Nietzsche and Kant on the development of Deleuze & Guattari's thinking. He also examines the wider implications of their work in revitalizing Marxism, environmentalism, feminism and cultural studies.